Measurement of spectral and polarization characteristics of parametric X-rays in a Si crystal; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 44, iss. 2 - Adishchev Yu. N. Yuri Nikolaevich; Verzilov V. A.; Potylitsyn A. P. Alexander Petrovich; Uglov S. R. Sergey Romanovich; Vorobiev S. A. Sergey Aleksandrovich (1989, 1989)
Title screen